The Effects Of Square Designs On User Behaviors: The Case Of Taksim Square - Yasar, Dilek; Yücel Caymaz, Gökçen Firdevs; Matin Aygören, Saba (Street Art & Urban Creativity, 2022)
The squares as indispensable open spaces in the sociological, physiological and psychological context of urban life, not only create common platforms for various activities, but also serve as a communication space between the city and its residents. Human beings are the primary factor of the squares. How square designs affect user behaviors is a crucial question. Accordingly, the present study focused on Taksim Square, one of the important squares of the historical city of Istanbul in sociological, cultural, political, and economic terms, and investigated the relationship between design and user behavior in this particular square. The present study adopted an observational research construct, where the study data were captured on the map of the square as user and action inputs, and analyzed in the context of circulation and usage. The results were indicative of the fact that users might tend to use the square as a transit route in such square designs that fail to offer sufficient space for activities, functional diversity, and urban fixtures. Nevertheless, the squares attracted users and channeled them to spending more time in the square in cases when decorative elements, greenery elements, green textures, and seating units were included in the design.